2021
DOI: 10.3390/nano11061382
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles and Graphene Oxide Flakes Enhance Cancer Cells’ Phagocytosis through Granzyme-Perforin-Dependent Biomechanism

Abstract: The study aimed to investigate the roles of gold nanoparticles (GNPs) and graphene oxide flakes (GOFs) as phagocytosis enhancers against cancer cells. The nanomaterials were characterized through SEM and UV-VIS absorptions. The GNPs and GOFs increased the macrophages’ phagocytosis ability in engulfing, thereby annihilating the cancer cells in both in vitro and in vivo conditions. The GNPs and GOFs augmented serine protease class apoptotic protein, granzyme, passing through the aquaporin class protein, perforin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Therefore, the surface modification of CNPs via decorating with metal (Ag, Au, and Pt) and metal oxide nanoparticles (ZnO, Fe 2 O 3 , and TiO 2 ) is the most functional methods to enhance the antibacterial performance of and reduce the adverse effects of the metal and metal oxide materials. Recently, the development of carbon nanostructures decorated with different types of NPs demonstrates a promising process for different applications [7][8][9][10]. Among them, copper materials demonstrated the ability to modify cancer cell metabolism and induce cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the surface modification of CNPs via decorating with metal (Ag, Au, and Pt) and metal oxide nanoparticles (ZnO, Fe 2 O 3 , and TiO 2 ) is the most functional methods to enhance the antibacterial performance of and reduce the adverse effects of the metal and metal oxide materials. Recently, the development of carbon nanostructures decorated with different types of NPs demonstrates a promising process for different applications [7][8][9][10]. Among them, copper materials demonstrated the ability to modify cancer cell metabolism and induce cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of antimicrobial activity for the CNF substrate was because the Cu2O-NPs were encapsulated inside the CNF matrix and not in contact with the pathogen cells. Although the nanostructure of carbon nanotube materials provided antimicrobial properties [17,[36][37], this CNF sample not exhibiting the zone of inhibition may be due to the larger diameter size of carbon fiber. Samadian et al [5] reported that the degree of genotoxicity for electro-spun CNFs derived from PAN followed by heat treatment may be less than that of traditional CNFs.…”
Section: Antimicrobial Activitymentioning
confidence: 89%
“…In recent years, among all noble metal nanoparticles, gold nanoparticles have received extensive attention owing to their biocompatibility, tunable surface plasmon resonance (SPR) and unique optoelectronic characteristics (Boisselier & Astruc, 2009 ; Zeiri et al., 2014 ). It has been reported that gold nanoparticles together with the micro-environmental stimuli could help activate the immune system (MacParland et al., 2017 ; Al-Omar et al., 2021 ). Furthermore, gold nanoparticles possess a rough surface with a high surface-to-volume ratio, enabling these particles with high cohesive ability to form various biomolecules, providing us an opportunity to biosynthesize nanocomposites with less toxicity (Ahn et al., 2018 ; Khan et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%